2000
DOI: 10.21236/ada383528
|View full text |Cite
|
Sign up to set email alerts
|

Adjudicative Guidelines and Investigative Standards in the Department of Defense

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden, to Department of Defense, Washington Headquarters Services, Directorate for I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Three studies have led to the conclusion that there is a need for a systematic approach to defining and measuring quality in adjudication within the DoD. Reports have indicated: (1) there may be differences in how senior adjudicators and CAF officials apply adjudicative guidelines (Carney & Marshall-Mies, 2000); (2) the department needs to institute "peer review" "to ensure that the work produced meets quality control standards (DoD Office of the Inspector General, 1998); and (3) the Department should establish "common quality assurance mechanisms to identify any problem areas needing clarifying guidance or training" (General Accounting Office, 2001). The current study was undertaken to develop a definition of adjudication quality and outline the basic requirements for assuring the quality of DoD adjudications.…”
Section: Executive Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies have led to the conclusion that there is a need for a systematic approach to defining and measuring quality in adjudication within the DoD. Reports have indicated: (1) there may be differences in how senior adjudicators and CAF officials apply adjudicative guidelines (Carney & Marshall-Mies, 2000); (2) the department needs to institute "peer review" "to ensure that the work produced meets quality control standards (DoD Office of the Inspector General, 1998); and (3) the Department should establish "common quality assurance mechanisms to identify any problem areas needing clarifying guidance or training" (General Accounting Office, 2001). The current study was undertaken to develop a definition of adjudication quality and outline the basic requirements for assuring the quality of DoD adjudications.…”
Section: Executive Summarymentioning
confidence: 99%
“…It can take up to three years for an adjudicator to become qualified for the full range of adjudicative issues. A recent PERSEREC report (Carney & Marshall-Mies, 2000) indicated that the civilian adjudication workforce has an average of 11 years of adjudicative experience. The civilian adjudicator workforce is currently being augmented by military reservists.…”
Section: Adjudicator Qualificationsmentioning
confidence: 99%
See 1 more Smart Citation